In situ Characterization of SiO2 Nanoparticle Biointeractions Using BrightSilica. (20th March 2014) - Drescher, Daniela; Zeise, Ingrid; Traub, Heike; Guttmann, Peter; Seifert, Stephan; Büchner, Tina; Jakubowski, Norbert; Schneider, Gerd; Kneipp, Janina
<x xml:space="preserve">Abstract</x> By adding a gold core to silica nanoparticles (BrightSilica), silica‐like nanoparticles are generated that, unlike unmodified silica nanoparticles, provide three types of complementary information to investigate the silica nano‐biointeraction inside eukaryotic cells in situ. Firstly, organic molecules in proximity of and penetrating into the silica shell in live cells are monitored by surface‐enhanced Raman scattering (SERS). The SERS data show interaction of the hybrid silica particles with tyrosine, cysteine and phenylalanine side chains of adsorbed proteins. Composition of the biomolecular corona of BrightSilica nanoparticles differs in fibroblast and macrophage cells. Secondly, quantification of the BrightSilica nanoparticles using laser ablation inductively coupled plasma mass spectrometry (LA‐ICP‐MS) micromapping indicates a different interaction of silica nanoparticles compared to gold nanoparticles under the same experimental conditions. Thirdly, the metal cores allow the investigation of particle distribution and interaction in the cellular ultrastructure by cryo nanoscale X‐ray tomography (cryo‐XT). In 3D reconstructions the assumption is confirmed that BrightSilica nanoparticles enter cells by an endocytotic mechanism. The high SERS intensities are explained by the beneficial plasmonic properties due to agglomeration of BrightSilica. The results have implications for the development of multi‐modal qualitative and quantitative characterization in comparative nanotoxicology and bionanotechnology.